USING WEBTOON COMICS AS AN ONLINE LEARNING MEDIA TO IMPROVE STUDENTS’ SPEAKING SKILLS - Aurelia Eka Putri (STKIP Subang, 2026)
The development of online learning media has opened new opportunities in language learning. Speaking is an essential skill for learners however it is often labeled as the most challenging skills in language learning. It is affected by several factors, such as low motivation, speaking anxiety, and non-contextual learning media. This study investigates whether the use of Webtoon comics as an online learning media would improve students’ speaking skills. Using quasi-experimental design, 69 vocational students were divided into experimental and control group. The experimental group were engaged with selected Webtoon comic entitled “Your Letter” as the intervention, while the control group received conventional learning process. Pre-test and post-test measured content, structure, and fluency in speaking. The results indicate that the students in experimental group demonstrate significant improvement in speaking achievement. These findings suggest Webtoon comics as an online learning media to improve speaking skills, it serves as an effective and interesting teaching aid.